ChemInform Abstract: Toward Molecular Catalysts by Computer. Issue 14 (April 2015) - Raugei, Simone; DuBois, Daniel L.; Rousseau, Roger; Chen, Shentan; Ho, Ming‐Hsun; Bullock, R. Morris; Dupuis, Michel
Abstract: Review: 41 refs.